Global regularity for a family of 3D models of the axi-symmetric Navier–Stokes equations. (4th April 2018) - Hou, Thomas Y; Liu, Pengfei; Wang, Fei
Abstract: We consider a family of three-dimensional models for the axi-symmetric incompressible Navier–Stokes equations. The models are derived by changing the strength of the convection terms in the axisymmetric Navier–Stokes equations written using a set of transformed variables. We prove the global regularity of the family of models in the case that the strength of convection is slightly stronger than that of the original Navier–Stokes equations, which demonstrates the potential stabilizing effect of convection.